2017
DOI: 10.1038/s41598-017-04308-1
|View full text |Cite
|
Sign up to set email alerts
|

Combination of a high-fat diet with sweetened condensed milk exacerbates inflammation and insulin resistance induced by each separately in mice

Abstract: Obesogenic diets increase body weight and cause insulin resistance (IR), however, the association of these changes with the main macronutrient in the diet remains to be elucidated. Male C57BL/6 mice were fed with: control (CD), CD and sweetened condensed milk (HS), high-fat (HF), and HF and condensed milk (HSHF). After 2 months, increased body weight, glucose intolerance, adipocyte size and cholesterol levels were observed. As compared with CD, HS ingested the same amount of calories whereas HF and HSHF ingest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 63 publications
(54 reference statements)
3
27
0
1
Order By: Relevance
“…The HFD group had the same final body weight as the HCD group, despite lower caloric intake. These results are in agreement with other studies indicating that calories in the form of fat favor higher fat deposition compared with a high-carbohydrate diet (8,20).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The HFD group had the same final body weight as the HCD group, despite lower caloric intake. These results are in agreement with other studies indicating that calories in the form of fat favor higher fat deposition compared with a high-carbohydrate diet (8,20).…”
Section: Discussionsupporting
confidence: 93%
“…As described in other reports (8,12,13), we previously demonstrated that a high-carbohydrate diet (HCD) given for 2 months leads to a similar body weight gain compared with a high-fat diet (HFD) in Swiss mice (14,15), allowing the evaluation of diet-induced changes in FA composition and inflammatory markers without the influence of obesity. In these studies, we reported changes in FA composition and inflammatory markers in the liver (14) and brain (15).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Pekerja beranggapan kental manis merupakan penyumbang kalsium. Berdasarkan penelitian Masi et al (2017) kental manis mengandung lebih tinggi gula dibandingkan dengan kalsium 23 . Selain itu, pekerja bagian perkantoran lebih cenderung berada di dalam ruangan dan sangat sedikit terkena sinar matahari.…”
Section: Hasil Dan Pembahasanunclassified
“…This suggests an imbalance in the antioxidant defense system in offspring of obese fathers. Inflammation of adipose tissue, a common feature of obesity, has been associated with insulin resistance and an imbalance of the antioxidant defense system (MASI et al, 2017;SURIYAPROM et al, 2019). Both have been implicated in several diseases, such as atherosclerosis, diabetes and obesity (SALTIEL;OLEFSKY, 2017;SURIYAPROM et al, 2019).…”
Section: Programming Effects Of Paternal Obesity In Female Offspring mentioning
confidence: 99%